Total revenue analysis (1994-1998) and projection (1999-2010) of private business firms in La Carlota City Negros Occidental a time-series approach - Juson, Carlos S. (1999)
This study is a combination of Economics and Management theories, concepts and models that is designed to meet the present challenges of our times. This study has successfully analyzed trend and seasonally of the total revenue of business firms in La Carlota City in different sectoral classifications. As a result, there was a domination of the total revenue of the industrial sector having an average contribution of 47% in the 5-years (1994-1995). During 1995, industrial sector ad suffered tremendous problems due to sugar crisis and internal troubles, but it had recovered from 1996-1998. Other sectors of business firms like commercial sector-23% service sector - 6.2%, financial sector 8.2%, agricultural sector .2%, Housing and real estate sector 10.2%, labor/construction sector - 4.0% and lastly the recreational sector had zero advantage percentage contribution for the past 5 years. The study had successfully forecasted the total revenue of of business firms from 1999-2010 using the simple exponential model and it found out that there will be a total revenue of 1,645,000,000 in the year 2010 of the trend and the forecast explained that there is an imbalance kind of growth and development in La Carlota City since only on sector is dominating as the biggest rvenue earner, the industrial sector. There must be an investment incentive policies that would encourage investors to invest in La Carlota City given in its strategic location.
Undergraduate Research Project (Mgt 200-Management Research). -- Miagao, Iloilo : UPV-CM, March 1999.